Malaise dan Lambang Kekayaan Ekonomi Penguasa Lokal di Palembang, 1929–1942 - Dedi Irwanto (Lembaran Sejarah, 2017)
This is an article on economic history, particularly on the economic growth of Palembang’sUluan local elites. But the main focus of the article is to understand and interpret other phenomenon that appeared as the product of that economic growth; its social-cultural implications that was present as a social reality of those economic conditions. It focuses on the creation of emblems of symbolic power in its political and economic manifestations. The emblems of economic wealth is seen as a symbol. As a symbol, this emblem represented meanings with several important functions, not merely as material collection, but also through a sociocultural lense; as the effort to create and contest with its peers or as an asimilative or adaptive process and a process of resistance to other groups that are ‘above’ its structure. The symbolic emblems of local power changed during the depression era of 1929. In a period where significant amount of wealth was lost, theuluan Palembang bucked the trend and appeared as new money (orang kaya baru) with all their new atributes of wealth.